Assessment of Interaction between Banking and Real Sectors of the Economy Based on the Convergence Effect - Kazarenkova, Natalya Petrovna; Kolmykova, Tatyana Sergeevna; Ovcharova, Olga Nikolaevna (International Journal of Economics and Financial Issues, 2015)
The main trends of the development of banking and real sectors of the economy in their structural interaction analyzes in the article. Factors of effective interaction were identified on base of analyze results besides the interdependence was shown between banking and real sectors of the economy. Modern conditions of post-crisis development of the economy determine the necessity of active use of bank resources to ensure uninterrupted financing of the real sector, which surplus funds serve as a resource base for commercial banks. That is why the use of convergence effect in improving the effectiveness of interaction of banking and real sectors of economy is appropriate. The article provides an assessment of the main directions of interaction of banking and real sectors of the economy and forms of the promising areas of cooperation. Keywords: Banking sector of the economy, real sector of the economy, interaction, forms of the interaction, potential of the development, convergence. JEL Classifications: G21, R30